Efek Temperatur Terhadap Bentuk Partikel Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Kulit Telur Itik Melalui Metode Presipitasi - Tanjung, Muhamad Adrian; A, Yelmida; Komalasari, Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Hydroxyapatite (Ca10(PO4)6(OH)2) is the most stable form of calcium phosphate, which is widely used in various medical applications, mainly in orthopedics and dentistry due to it’s similarities with inorganic mineral component of bone and teeth. However, in spite of chemical similarities, mechanical performance of synthetic hydroxyapatite is very poor compared with that of natural bone. It is possible to improve the properties of hydroxyapatite ceramics by controlling important parameters of powder precursors such as particle size, particle shape and agglomeration. Generally, natural or synthesized hydroxyapatite particles have rod-like and spherical-like. Different shapes of hydroxyapatite will affect biological response to human body, and the adaptation of osteoblast with hydroxyapatite. In this work, the synthesis of hydroxyapatite with various shapes has been done succesfully with the aid of precipitation method, by controlling the temperature. Spherical-like hydroxyapatite was synthesized at 30oC, rod-like hydroxyapatite was synthesized at 50oC and 70oC, and needle-like hydroxyapatite was synthesized at 90oC. FTIR analysis showed that the apatite compound has been formed with the absorption of PO4 3- and OH - ion at the wave number 1027.64, 1026.96, and 3301.69 cm-1. XRD analysis showed the similarities with standard hydroxyapatite ICDD 01-074-0566. The degree of crystallinity will be higher as long as temperature increased.Keywords: hydroxyapatite, particle shape, duck eggshells, temperature, precipitation method